1991
DOI: 10.1111/j.1834-7819.1991.tb01340.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cheese on dental caries: A review of the literature

Abstract: The relationship between nutrition and dental health has been a topic of interest for many years. Recently, the cariostatic properties of cheese have been the subject of intensive research. Most of these studies suggest that the use of cheese as the final food in a meal will help to reduce caries. Several mechanisms by which cheese may reduce enamel demineralization have been proposed. Chewing cheese stimulates saliva flow. The alkaline nature of saliva buffers the acids formed in plaque. There is also an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
10

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 29 publications
2
33
0
10
Order By: Relevance
“…Since A. viscosus Nyl produces a neuraminidase (unpublished observation), it is assumed that this enzyme unmasks the Gals 1-3 GalNAc sequences, which are known to act as ligands for the Actiinoniyces type 2 fimbriae (McIntire et al, 1983;Str6mberg and Boren, 1992;Stromberg ct al., 1992). A reduction of mutans streptococci has not been consistently observed in all experimental rat caries studies (for a review, see Herod, 1991;Reynolds ct al., 1995). This, however, is no surprise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since A. viscosus Nyl produces a neuraminidase (unpublished observation), it is assumed that this enzyme unmasks the Gals 1-3 GalNAc sequences, which are known to act as ligands for the Actiinoniyces type 2 fimbriae (McIntire et al, 1983;Str6mberg and Boren, 1992;Stromberg ct al., 1992). A reduction of mutans streptococci has not been consistently observed in all experimental rat caries studies (for a review, see Herod, 1991;Reynolds ct al., 1995). This, however, is no surprise.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since Lady May Mellanby (1929,1930) proposed milk as an important nutritional factor affecting pre-eruptive tooth mineralization and post-eruptive caries resistance, the relationship between milk and caries has been examined from various angles [for a review, see Reynolds and Storey (1979) and Herod (1991Herod ( ,1994]. Although Mellanby's theory was not tenable, numerous animal studies have demonstrated that milk and milk products (primarily cheese) have a protective effect against the development of dental caries (Bevetta and McClure, 1957;Shaw et al, 1959;Dreizen et al, 1961; Reynolds and Del Rio, 1984;Harper et al, 1986;Reynolds and Black, 1987;Bowen and Pearson, 1993;Mundorff-Shrestha et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…14 - 19 Erickson et al 16 investigated the caries-related properties of whole milk and infant formulas. Although milk supported bacterial growth, it had a high buffering capacity and required substantially more time than sucrose and some infant formulas to produce caries.…”
mentioning
confidence: 99%
“…ment of caries lesions. A considerable amount of research has been conducted on investigating the influence of various foods on caries development [22][23][24] It has also been discussed, that milk and milk products may have a cariostatic effect 19,20,25 The cariostatic effect of milk and milk products may be due to their high content of Ca and P ions, the buffer capacity, or to the content of casein phosphopeptides 17,20,26 . However, there has been a controversial discussion about the fluoride availability in milk 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Enamel remineralization is not only dependent on bio-availability of fluoride but also on the calcium and phosphorus content in the oral cavity. Milk contains relatively high concentrations of calcium and phosphorus and may therefore be an ideal carrier for remineralization of enamel 16,17 It has been debated whether milk alone and milk products have a cariostatic effect [18][19][20][21] Recent investigations have shown that fluoridated milk is more effective in caries inhibition than milk alone 5,6,8,9 Dietary regimes and fluoride bioavailability are therefore the keystone for caries inhibition and remineralization.…”
Section: Introductionmentioning
confidence: 99%